DEVELOPMENT AND EVALUATION OF A VERSATILE CONTROL SYSTEM IN AN ADAPTABLE MULTI-LEGGED ROBOT USING A MODIFIED PEAUCELLIER-LIPKIN MECHANISM - Papatla Rajesh (Journal of Mechanics of Continua and Mathematical Sciences)
The present work in bio-inspired robotics explores the design and implementation of a novel-legged robotic system featuring a modified PeaucellierLipkin mechanism with three control points for a single degree of freedom. The emphasis is placed on the robot’s adaptability to various walking gaits in different environments. The paper delves into the robot’s design, construction, and control system, which includes the application of PID control for enhanced stability and efficiency in mimicking biological locomotion. The primary aim is to demonstrate a robot capable of adjusting its form and function for diverse operational challenges, enhancing robotic mobility. The design also addresses repeatability issues, ensuring consistent performance across various tasks and conditions, contributing to the robot’s reliability and practical applicability in real-world scenarios.